Stable analogues of nojirimycin – synthesis and biological evaluation of nojiristegine and manno-nojiristegine1. Issue 37 (7th October 2015) - Viuff, Agnete H.; Besenbacher, Louise M.; Kamori, Akiko; Jensen, Mikkel T.; Kilian, Mogens; Kato, Atsushi; Jensen, Henrik H.
<x xml:space="preserve">Abstract</x> Two novel iminosugars called nojiristegines, being structural hybrids between nor-tropane alkaloid calystegine and nojirimycins, have been synthesised and the hemiaminal functionality found to be stable.